Ferromagnetic behavior with incomplete saturation of the ?-Al5Fe2 intermetallic compound synthesized by the arc-melting technique - Gálvez-Breña S. (2020)
In this work, we study the synthesis process and structural and magnetic characterization of the ?-Al5Fe2 intermetallic alloy obtained by the arc-melting technique. Subsequently, in order to obtain homogeneous crystalline phase, all melted samples were annealed at 847?C during 2 days, and then quenched into water. The structural and micro-structural characterization of the samples were performed by X-ray diffraction and,57Fe transmission Mössbauer spectroscopy, while the morphological study was performed using scanning electron microscopy. Moreover, magnetic characterization was carried out using vibrating sample magnetometer. X-ray fluorescence was employed for elemental characterization. The results indicate that it is possible to employ the arc-melting technique to synthesize the ?-Al5Fe2 intermetallic phase with high structural quality: orthorhombic crystalline structure and Cmcm space group. It has also been found that the ?-Al5Fe2 alloy has a ferromagnetic behavior with incomplete saturation. On the other hand, studies of the local structure around iron atoms show topological disorder due to the fractional occupations inherent in the structure of the intermetallic under study. Finally, the compositional analysis indicates that the material is within the allowed homogeneity range.